Fundamental Human Rights of Women: Islamic Panacea for Rights Abuses - Rafatu Abdul Hamid (Millati: Journal of Islamic Studies and Humanities, 2019)
Fundamental human rights provisions had continued to feature very prominently in the successive constitutions of the Federal Republic of Nigeria. In addition, there had been a rise in the activities of human right groups in Nigeria in order to ensure the protection of fundamental human rights of all people. Despite all these, women fundamental human rights abuse was on the increase in Nigeria. The case of domestic violence, kidnapping, sexual harassment, women trafficking, killings, denial of the right to Education etc, are common occurrences. These abuses among others are responsible for physical and psychological underdevelopment of women and girl child which in turn affects their input in the development of their nation. It is against this backdrop that this paper examines two abuses of women fundamental human rights: abuse of right to life and education. The paper also discusses the instrumentality of effective use of the Islamic panacea in tackling the abuse of women fundamental human rights in Nigeria. The study relied on primary and secondary sources of information. It concludes by recommending that, for the full observance of human rights, an international control must be set up to supervise enforcement, as well as the education of the women and society in general.